MODERN APPROACH TO ASSESS THE ASTHMA CONTROL AND TREATMENT EFFICASY IN DIFFERENT PHENOTYPES BY ENDOTHELIAN DISFUNCTION - S. A. Pribylov; N. N. Pribylova; O. Iu. Makhova; T. A. Barbashina; L. V. Samosudova (SINAPS LLC, 2017)
The aim of this study is to measure the level of the endothelin-1 in blood samples and to assess vasoactive function of the endothelial in asthma patients with different phenotypes and to develop the methods of the objective assess of the ongoing treatment. Materials and methods. 119 asthma patients were separated into several phenotypes: patients with atopic asthma (60 pat); patients with ACOS (35 pat); asthma with obesity (24 pat). In all patients endothelium-dependent vasodilation and plasma level of endothelin-1 were assessed. Results. Endothelial dysfunction revealed in all asthma phenotypes. The highest level of the endothelin-1 shown in ACOS patients. In patients which achieved asthma control during three month of the anti-inflammatory therapy showed decreasing of the endothelin-1 level by 1,5 times in comparison with basic level (0,35 ± 0,06 fmol/ml and 0,64 ± 0,15 fmol/ml respectively, р < 0,01). But in patients with persistent symptoms and/or without lung function improvement the level of the endothelin-1 was not decreased significantly. Conclusions. Change of the functional conditions of the endothelial depend on the time and severity and phenotype of the asthma. The endothelin-1 level and the endothelium-dependent vasodilatation assess on the course of the treatment allow to reveal success of this anti- inflammatory therapy.